2018
DOI: 10.1007/s00148-018-0691-2
|View full text |Cite
|
Sign up to set email alerts
|

Rising longevity, fertility dynamics, and R&D-based growth

Abstract: This study constructs an overlapping-generations model with endogenous fertility, mortality, and R&D activities. We demonstrate that the model explains the observed fertility dynamics of developed countries. When the level of per capita wage income is either low or high, an increase in such income raises the fertility rate. When the level of per capita wage income is in the middle, an increase in such income decreases the fertility rate. The model also predicts the observed relationship between population grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This simplification allows us to undertake a simple analysis. Futagami and Konishi (2017) analyze the situation in which the old-age survival rate depends on the variety of goods in R&D-based growth model without human capital.…”
Section: Market Equilibriummentioning
confidence: 99%
“…This simplification allows us to undertake a simple analysis. Futagami and Konishi (2017) analyze the situation in which the old-age survival rate depends on the variety of goods in R&D-based growth model without human capital.…”
Section: Market Equilibriummentioning
confidence: 99%
“…Due to real wage growth, this change, eventually, leads to fertility decline. 2 See, e.g., Bongaarts and Sobotka (2012), Day (2016), Dominiak et al (2015), Futagami and Konishi (2019), Goldstein et al (2009), Hirazawa and Yakita (2017), Lacalle-Calderon et al (2017), Luci and Thévenon (2011), Mavropoulos and Panagiotidis (2021), Myrskylä et al (2009), and Nakagaki (2019), and Ohinata and Varvarigos (2019). , 1960, -2010, the following countries are included: Austria, Australia, Belgium, Denmark, Finland, France, Germany, Greece, Iceland, Ireland, Italy, the Netherlands, Norway, Portugal, Spain, Sweden, the UK, and the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the literature does not provide a clear explanation for the factors causing a rebound in the average fertility rates. 3 Although Day (2016), Futagami andKonishi (2019), andHirazawa andYakita (2017), and Ohinata and Varvarigos (2019) achieved significant progress in analyzing the forces behind the recent fertility rebound, clear insights into some important aspects of this phenomenon are still missing. These studies on the fertility rebound identified that the decreasing relative costs of child-rearing (childcare and education costs) and longevity are preventing further decline or driving the fertility rates upward.…”
Section: Introductionmentioning
confidence: 99%
“…In Castello-Clement and Domenech (2008), adult individuals' survival probability depends on the human capital of their parents. In Futagami and Konishi (2019), the probability of survival from adulthood to old age depends on the wage rate.…”
Section: Introductionmentioning
confidence: 99%